Design and cost performance of WDM PONs for multi-wavelength users. (6th January 2009) - Schussmann, Jurgen; Schirl, Thomas
In many research labs, WDM PON access networks are considered as the next generation optical access. WDM PONs are more adaptable to future technologies than conventional PONs due to their high transmission capacity and their optical transparency. An elementary design concept is the paradigm that defines at least one wavelength for each user. A design tool is presented to analyse all technologically feasible WDM PON architectures and the cost performance based on an optical routing device, the waveguide grating router.